Innovation of Mobile Science Laboratories as a Solution to Access to Practical Learning in Schools: A Case Study at an Education Quality Assurance Center in Banten, Indonesia - Pamungkas, Aan Subhan; Muslim, Suyitno; Khaerudin, Khaerudin (International Journal of STEM Education for Sustainability, 2025)
Inequality of access to laboratory facilities is one of the main challenges in science learning in schools, especially in areas with limited infrastructure. This study aimed to describe and analyze the innovation of the Mobile Science Laboratory implemented by an Education Quality Assurance Center in Banten, Indonesia as an alternative solution in expanding access to practical learning. This study used a qualitative approach with a case study type. Data collection techniques were carried out through interviews with program managers and documentation analysis. The results of the study indicate that the mobile science laboratory program contributes to expanding access to practical work for students in schools that do not have laboratory facilities, increasing student engagement in science learning, and strengthening teachers' pedagogical capacity. The main challenges in implementation include time constraints, school facility conditions, teacher readiness, and logistics. Supporting factors for the success of the program include the institutional commitment of an Education Quality Assurance Center, adaptive program design, and enthusiasm from target schools. This study recommends integrating the program with teacher training, regional policy support, and developing a replication model in other provinces.